Exploring the Influence of Continuous Professional Education in Fostering Leadership Development in Universities - Ibrahim, Asmawi; Rami, Ahmad Aizuddin Md; Yaakob, Mohd Faiz Mohd; Olaitan, Ahmed Ahmed (Journal of Ecohumanism, 2024)
Continuing Professional Education (CPE) program has been in the forefront of Malaysia’s government-supported professional development initiative, which aims to encourage all civil servants to make headway in their studies. The study was undertaken to examine the professional development of civil servants at Universiti Utara Malaysia (UUM), Universiti Sultan Zainal Abidin (UniSZA) and University Putra Malaysia (UPM), with regard to the influence of leadership development, innovation, proficiency and education. Civil servants who partook in the Continuing Professional Education (CPE) program at these Universities were purposely selected for the study. To gather data, we conducted two FGDs involving a total of 12 participants. The insights obtained from the research findings divulged and provided us with a wealth of information. Based on the findings, quest to achieve professional growth innovational culture and leadership development was found to influence the civil servants in joining the CPE.